A Multiple Leader Stackelberg Model and Analysis - Sherali, Hanif D. (Operations Research, 1984)
This paper presents a new multiple leader-follower model that is a consistent extension of Stackelberg's leader-follower duopoly. The development contrasts with other existing extensions by demonstrating how the leader-firms can utilize the true reaction curve of the follower-firms; it also provides sufficient conditions for some useful convexity and differentiability properties of this function. For the proposed model, we conduct a static analysis and discuss the existence, uniqueness, and computation of an equilibrium solution, as well as study certain issues regarding the relative profits of leader and follower-firms. Since the Cournot oligopoly and the Stackelberg leader-follower models are special cases of this model, the analysis in this paper hopefully provides some further insights about these types of models.